(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
The periphrasis “sthā- + present participle” was described by Berthold Delbrück in his Altindische Syntax [1888]. Such a construction would indicate the persistency in the action and the verb ‘stay’ would play the role of an auxiliary form. The present paper analyses a group of brāhmanic passages in order to confirm the scholar’s hypothesis (which was based on two sole examples) and enlarge the corpus known so far: in fact, brāhmanic prose shows texts which are less ambiguous and more perspicuous than poetry. KEYWORDS: Vedic, aspectual periphrases, syntax, stay, auxiliary verbs